Benthic habitat mapping using landsat 8 satellite imagery / Muhamad Faizul Azhar - Azhar, Muhamad Faizul (2020)
Benthic habitat mapping is a spatial representation of physically distinct areas of seafloor that are associated with particular groups of plants and animals. Usually benthic habitat maps can determine the distribution and abundance of species and can identify critical or sensitive habitats. It also can summarize the physical and biological resources of a region. There are many approaches to map a benthic habitat and this study used Landsat 8 satellite imagery as it has a limited research on this field. Landsat 8 satellite imagery data is easily accessible and use no cost to extract the sediment types data. Benthic habitat was mapped by using four different band composites of Landsat 8 satellite imagery. Each band composites will be produced different type of benthic habitat map. The area of sediment classification is different for each band composites. Acoustic Ground Discrimination System was used to verify the benthic habitat developed by different band composites and the most similar with it was determined by using map accuracy assessment and Cohen’s Kappa coefficient. The location of this study was at Pulau Langgun, Pulau Langkawi and there were four types of sediment classification which were wred on sand, coral, medium sand and mud. From the sediment classification obtained, it can help to predict the living habitat and its distribution and abundance and develop a reliable benthic habitat map at that particular area.